Combustion and performance characteristics of air-fuel mixtures ignited by means of photo-thermal ignition of Nano-Energetic Materials. (September 2017) - Carlucci, A. Paolo; Ficarella, A.; Laforgia, D.; Strafella, L.
Abstract: This work presents an experimental investigation to determine the performance and characteristics of the combustion process triggered by a new ignition system based on photo-thermal effect, observed when nano-Energetic Materials are exposed to a flash light. The resulting combustion process has been compared with the one obtained using the spark-plug traditionally used in spark ignition engines. Results showed that the photo-thermal ignition determines higher combustion pressure gradient, peak pressure, total heat released, fuel combustion efficiency, and a shorter ignition delay and combustion duration compared with the spark ignition, for all the tested fuels and air-fuel ratios.